The Innovator Role of the School Principal in Supporting the Implementation of the Eight Dimensions of Graduate Profiles through Co-Curricular Programs at MI YAPPI Peyuyon Semanu Gunungkidul - Asih Suprihatin; Rahmat Mulyono; Saryanto (Universitas Pakuan, 2026)
This study aims to analyze comprehensively the innovator role of the school principal in implementing the eight dimensions of graduate profiles through co-curricular programs at MI YAPPI Peyuyon, Semanu, Gunungkidul. The primary focus of this research is how leadership innovation can address educational challenges in the era of the Merdeka Curriculum, which demands flexibility and contextualization of character values within habituation activities. The research method employed is descriptive qualitative with a case study approach to explore leadership phenomena naturalistically. Data collection was conducted through in-depth interviews with key informants, participatory observation of students’ routine activities, and documentation studies of curriculum documents and character portfolios. Data analysis utilized the interactive model of Miles, Huberman, and Saldana, which includes data condensation, data display, and conclusion drawing. The findings indicate that the school principal acts as a catalyst for innovation through three primary strategies: 1) Policy transformation integrating the madrasah vision with national graduate profile indicators; 2) Development of a collaborative school ecosystem involving synergy among educators, educational staff, and parents; and 3) Utilization of local resources (Semanu local wisdom) as the foundational material for co-curricular programs. The findings further reveal that the implementation of the eight dimensions of graduate profiles (faith, citizenship, critical reasoning, creativity, collaboration, independence, health, and communication) demonstrates a significant improvement in the habituation of students’ character behavior. This is evidenced by the increasing student independence in the learning process and the strengthening of communication ethics. Despite being constrained by limited rural infrastructure and digital access, the school principal’s innovation in the form of “contextual instructional modification” proved capable of sustaining program continuity. This study recommends the necessity of strengthening innovation literacy among school principals in rural areas in order to optimize environmental potential as a medium for authentic character development.